ESTUDIO DE FACTIBILIDAD PARA LA IMPLEMENTACIÓN DE UNA DISCOTECA SILENCIOSA EN LA CIUDAD DE LOJA - Silva García, Medardo Ángel (2019)
The purpose of this research is to determine the feasibility of the implementation of a silent nightclub in the city of Loja, being an innovative service in the Lojano market, this study allowed to identify favorable conditions for its development. Within the structure and development of this project, a methodology was used in which the materials, methods, techniques and procedures applied during the development of the thesis were determined. The results were obtained through the realization of a diagnosis that covers as a first point the execution of the market study where it was possible to determine the existing demand in the market, as well as the offer, a marketing plan was proposed that will allow the growth of the service, then the technical study was carried out to determine the size of the project, its installed capacity to provide an excellent service, the location and its legal organization, the respective organization charts and functions manual was elaborated, followed by the financial study that allowed knowing the total investment, cost and income budgets as the main basis of the project, the financial evaluation was finally executed to establish the profitability and feasibility that the project will have at the moment of being implemented. In the results, the derivations of the surveys applied to the plaintiffs and bidders of this study to those over 18 years of age in the city of Loja, through tables and statistical graphs with their respective interpretation, are disclosed. In the discussion, the market study was first structured, through which the potential, real, effective demand and the average consumption per capita was determined, an analysis and projection of the offer was developed, and the respective marketing plan; in the technical study, the size and location were determined, the organizational study where the legal framework is included. - 5 - Finally, according to the results obtained, the feasibility of the project was determined, for which the following indicators were analyzed: The Net Present Value of $ 165997,46; Internal Rate of Return of 54.61%; Benefit Cost Ratio is $ 1.30 for every dollar invested the company earns 0.30 cents; Period of Capital Recovery which is 4 years and 8 months; Through the Sensitivity Analysis it was determined that the project can support an increase in costs of 15% with the decrease in revenues of 8.9%, for which the project is feasible, whose conclusions and recommendations so determine, attaching the bibliography consulted with their respective annexes